A novel drug‐coated scoring balloon for the treatment of coronary in‐stent restenosis: Results from the multi‐center randomized controlled PATENT‐C first in human trial. Issue 1 (2nd September 2015) - Scheller, Bruno; Fontaine, Tobias; Mangner, Norman; Hoffmann, Stefan; Bonaventura, Klaus; Clever, Yvonne P.; Chamie, Daniel; Costa, Ribamar; Gershony, Gary; Kelsch, Bettina; Kutschera, Maren; Généreux, Philippe; et al.
Abstract : Background: Scoring balloons produce excellent acute results in the treatment of in‐stent restenosis (ISR), fibro‐calcific and bifurcation lesions but have not been shown to affect the restenosis rate. A novel paclitaxel‐coated scoring balloon (SB) was developed and tested to overcome this limitation. Methods and Results: SB were coated with paclitaxel admixed with a specific excipient. Patients at four clinical sites in Germany and one in Brazil with ISR of coronary bare metal stent (BMS) were randomized 1:1 to treatment with either a drug‐coated or uncoated SB. Baseline and 6‐month follow‐up quantitative coronary angiography was performed by an independent blinded core lab and all patients will be evaluated clinically for up to one year. The primary endpoint was angiographic in‐segment late lumen loss (LLL). Secondary endpoints included the rate of clinically driven target lesion revascularization (TLR), composite of major adverse cardiovascular events (MACE), stent thrombosis and other variables. Sixty‐one patients were randomized (28 uncoated and 33 drug‐coated SB); mean age 65 years, males 72%, and presence of diabetes 39%. At 6‐month angiography, in‐segment LLL was 0.48 ± 0.51 mm in the uncoated SB group versus 0.17 ± 0.40 mm in the drug‐coated SB group ( P  = 0.01; ITT analysis). The rate of binary restenosis was 41% in the uncoated SB group versus 7% in the drug‐coated SB group ( P  = 0.004). The MACE rate was 32% with the uncoated SB vs. 6% in the drug‐coated SB group ( P  = 0.016). This difference was primarily due to the reduced need for clinically driven TLR in the coated SB group (3% vs. 32% P  = 0.004). Conclusions: A novel paclitaxel‐coated coronary SB has been developed and successfully used in a first‐in‐human randomized controlled trial [ClinicalTrials.gov Identifier: NCT01495533]. © 2015 Wiley Periodicals, Inc.